The Earliest Fleshy Cone of Ephedra from the Early Cretaceous Yixian Formation of Northeast China - Yang, Yong (Public Library of Science, 2013)
Bracts of female cones of extant gymnosperm Ephedra (Joint fir) are either colorful and fleshy (section Ephedra), or dry-winged and membranous (section Alatae), or dry and coriaceous (section Asarca), which have played a crucial role in long-distance seed dispersal that is responsible for a wide distribution of the genus in semiarid and arid areas of Eurasia, North Africa, North America, and South America. Recent molecular systematic studies on Ephedra have suggested that the fleshy bracts in character evolution may be plesiomorphic relative to the dry, membranous and coriaceous bracts. However, little is known about when the fleshy bracts of Ephedra have made their debut in the geological past. Herein, we describe a novel, fleshy bract-bearing female cone macrofossil from the Early Cretaceous (ca. 120—125 Ma) Yixian Formation in Liaoning, northeastern China. This cone bears three ellipsoid seeds subtended by only one whorl of fleshy bracts. Each seed has a thin outer envelope and an inner integument that extends upward and passes through the opening of the outer envelope, forming a thin and straight micropylar tube. Such a syndrome shows the closest similarity to an extant triovulate species Ephedra intermedia in the section Ephedra, but the latter bears a whorl of terminal fertile bracts and more than one whorl of inferior sterile bracts, and a thick outer envelope. Hence, we establish a new fossil species Ephedra carnosa. Our discovery provides the first direct macrofossil evidence for the previous molecular systematics of Ephedra, implying that the origin of fleshy bracts in Ephedra should not have been later than that of the membranous and coriaceous bracts by at least the Early Cretaceous.